Shape optimisation of two-dimensional structures using isogeometric analysis. (2017) - Ummidivarapu, Vinay K.; Voruganti, Hari K.
Structural shape optimisation is the important stage of a design process. It reduces the overall design cycle time, weight and cost of the structure. The main modules of structural shape optimisation are geometric modelling, analysis technique and optimisation procedure. Since shape optimisation is an iterative process, it is recommended that all the three modules bear a similar framework. In the traditional FEA-based shape optimisation, the geometric modelling and analysis modules are based on different frameworks and lead to difficulties like meshing, remeshing, loss of geometric data, abnormal optimal shapes, etc. Isogeometric analysis (IGA) would resolve the above issues by integrating both modelling and analysis into a unified framework. In this work, isogeometric analysis is applied for shape optimisation of two-dimensional structures and the results are presented. The IGA optimised results show that the difficulties of FEA-based shape optimisation are eliminated. Numerical results indicate the applicability of the method.